2000
DOI: 10.2337/diabetes.49.11.1766
|View full text |Cite
|
Sign up to set email alerts
|

Beacon: a novel gene involved in the regulation of energy balance.

Abstract: The hypothalamus plays a major role in the control of energy balance via the coordination of several neuropeptides and their receptors. We used a unique polygenic animal model of obesity, Psammomys obesus, and performed differential display polymerase chain reaction on hypothalamic mRNA samples to identify novel genes involved in obesity. In this study, we describe a novel gene that encodes a small protein we have termed "beacon." Beacon mRNA gene expression in the hypothalamus was positively correlated with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 0 publications
1
54
0
Order By: Relevance
“…In this connection, we remind that beacon, a ubiquitin-like protein (10)(11)(12) expressed in the rat adrenal cortex (13,14), has been found to inhibit the growth of cultured adrenocortical cells (15). Furthermore, it has been recently demonstrated that in the regenerating rat adrenal cortex the expression of the beacon gene is inversely correlated with the proliferative activity of adrenocortical cells (16).…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, we remind that beacon, a ubiquitin-like protein (10)(11)(12) expressed in the rat adrenal cortex (13,14), has been found to inhibit the growth of cultured adrenocortical cells (15). Furthermore, it has been recently demonstrated that in the regenerating rat adrenal cortex the expression of the beacon gene is inversely correlated with the proliferative activity of adrenocortical cells (16).…”
Section: Introductionmentioning
confidence: 99%
“…It may be of interest that the propensity to diabetes in the Mexican-American population has also been ascribed by Stern et al (1996) to the effect of a major gene which is dominant on the background of environmental predisposition. Although several genes related to energy balance and hyperglycaemia have been already isolated in specific tissues of Psammomys (Collier et al, 2000;Walder et al, 2002), our main conclusion is to challenge the polygenic approach to the development of insulin resistance and T2D. We have shown that, in an established dietary regimen defined by us, a major gene comes into play.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the beacon gene, which encodes a highly conserved 73 amino acid protein, was shown to be overexpressed in the hypothalamus of obese, outbred P. obesus relative to their lean, outbred littermates. 8 Expression of beacon in the hypothalamus was correlated with body fat content in P. obesus. Furthermore, immunohistochemical studies localized beacon expression to the retrochiasmatic area of the hypothalamus, a region that is thought to be involved in the regulation of energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…Co-administration of beacon and NPY for 7 days resulted in a profound increase in food intake and body weight that was significantly greater than expected given the results of separate administration of NPY and beacon. 8 Therefore it was suggested that part of beacon's actions are mediated through the NPY pathway, but beacon also acts independent of NPY to increase food intake and body weight. Using indirect calorimetry, it was shown that i.c.v.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation